Analysis of Mrgprb2 receptor-evoked Ca2+ signaling in bone marrow derived (BMMC) and peritoneal (PMC) mast cells of TRPC-deficient mice - Tsvilovskyy, Volodymyr; Solís López, Alejandra; Almering, Julia; Richter, Christin; Birnbaumer, Lutz; Dietrich, Alexander; Freichel, Marc (Frontiers in immunology, 2020)
Mast cells are a heterogeneous group of immune cells. The simplest and commonly accepted classification divides them in two groups according to their protease content. We have compared the action of diverse secretagogues on bone marrow derived (BMMC) and peritoneal (PMC) mast cells which represent classical models of mucosal and connective tissue type mast cells in mice. Whereas, antigen stimulation of the Fc epsilon RI receptors was similarly effective in triggering elevations of free intracellular Ca2+ concentration ([Ca2+](i)) in both BMMC and PMC, robust [Ca2+](i) rise following Endothelin-1 stimulation was observed only in a fraction of BMMC. Leukotriene C4 activating cysteinyl leukotriene type I receptors failed to evoke [Ca2+](i) rise in either mast cell model. Stimulation of the recently identified target of many small-molecule drugs associated with systemic pseudo-allergic reactions, Mrgprb2, with compound 48/80, a mast cell activator with unknown receptor studied for many years, triggered Ca2+ oscillations in BMMC and robust [Ca2+](i) rise in PMCs similarly to that evoked by Fc epsilon RI stimulation. [Ca2+](i) rise in PMC could also be evoked by other Mrgprb2 agonists such as Tubocurarine, LL-37, and Substance P. The extent of [Ca2+](i) rise correlated with mast cell degranulation. Expression analysis of TRPC channels as potential candidates mediating agonist evoked Ca2+ entry revealed the presence of transcripts of all members of the TRPC subfamily of TRP channels in PMCs. The amplitude and AUC of compound 48/80-evoked [Ca2+](i) rise was reduced by similar to 20% in PMC from Trpc1/4/6(-/-) mice compared to Trpc1/4(-/-) littermatched control mice, whereas Fc epsilon RI-evoked [Ca2+](i) rise was unaltered. Whole-cell patch clamp recordings showed that the reduction in compound 48/80-evoked [Ca2+](i) rise in Trpc1/4/6(-/-) PMC was accompanied by a reduced amplitude of Compound 48/80-induced cation currents which exhibited typical features of TRPC currents. Together, this study demonstrates that PMC are an appropriate mast cell model to study mechanisms of Mrgprb2 receptor-mediated mast cell activation, and it reveals that TRPC channels contribute at least partially to Mrgprb2-mediated mast cellactivation but not following Fc epsilon RI stimulation. However, the channels conducting most of the Ca2+ entry in mast cells triggered by Mrgprb2 receptor stimulation remains to be identified.
Im Titel ist "2+" hochgestellt
Gesehen am 17.06.2020